1990
DOI: 10.1177/070674379003500111
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Relating to Satisfactory Post-Discharge Community Maintenance of Chronic Psychotic Patients

Abstract: The length of time a group of 70 psychiatric patients could be maintained in the community following discharge from a provincial hospital was found to be significantly related to post-discharge compliance with medication and to the level of discharge planning (well planned versus unplanned, or patient prematurely self-discharged against medical advice). Various demographic and clinical variables were unrelated to the length of post-discharge survival in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…In a recent study into schizophrenic relapse, Hirsch et al (1996 , p. 49) found that ‘patients who continued on regular medication had 80% less risk of relapse than those who had been withdrawn from medication either by choice or under double‐blind controlled [research] conditions’. Compliance with medication following discharge from hospital in patients suffering from schizophrenia or bipolar affective disorder was also found to be ‘correlated significantly with longer stays in the community’ ( Fernando, Velamoor, Cooper & Cernovsky, 1990, p. 72).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study into schizophrenic relapse, Hirsch et al (1996 , p. 49) found that ‘patients who continued on regular medication had 80% less risk of relapse than those who had been withdrawn from medication either by choice or under double‐blind controlled [research] conditions’. Compliance with medication following discharge from hospital in patients suffering from schizophrenia or bipolar affective disorder was also found to be ‘correlated significantly with longer stays in the community’ ( Fernando, Velamoor, Cooper & Cernovsky, 1990, p. 72).…”
Section: Introductionmentioning
confidence: 99%
“…Die Einstufung der Compliance erfolgt ebenfalls nach unterschiedlichen Kriterien [39,43,45]. Die Patientenkollektive sind z. T. diagnostisch sehr heterogen [41,44,46] oder zeigen ganz unterschiedliche Krankheitsverläufe; so werden entweder ausschlieûlich chronisch Kranke [40] bzw. solche mit mindestens einem stationären Aufenthalt in der Vorgeschichte [38,45,46] oder Patienten mit Erstmanifestationen und intermittierenden Verläufen eingeschlossen [41,42,44].…”
Section: Diskussionunclassified
“…Die Patientenkollektive sind z. T. diagnostisch sehr heterogen [41,44,46] oder zeigen ganz unterschiedliche Krankheitsverläufe; so werden entweder ausschlieûlich chronisch Kranke [40] bzw. solche mit mindestens einem stationären Aufenthalt in der Vorgeschichte [38,45,46] oder Patienten mit Erstmanifestationen und intermittierenden Verläufen eingeschlossen [41,42,44]. Einige Studien befassen sich ausschlieûlich mit stationären, andere wiederum mit Patienten in einem ambulanten Setting [43,45].…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Discharge planning procedures were first developed by general hospitals (Kadushin and Kulys 1993), and are required by the Joint Commission on Accreditation of Health Care Organizations for both hospitals and behavioral health organizations (JCAHO 2003). The literature on discharge planning and homelessness includes various explorations about the transition to outpatient services and its impact on subsequent hospitalizations (Caton 1981;Fernando et al 1990;Hogarty 1972;Lurie et al 1981;Rock 1987). Clinical experience shows that lack of proper planning increases the chance that people will return to jails or mental health facilities, or relapse into problem behaviors (Community Shelter Board 2002).…”
Section: Introductionmentioning
confidence: 99%